Case-based review: ependymomas in adults. Issue 3 (24th July 2018) - Cachia, David; Johnson, Derek R; Kaufmann, Timothy J; Lowe, Stephen; Andersen, Samuel; Olar, Adriana; Cooper, Samuel Lewis; Frankel, Bruce M; Gilbert, Mark R
Abstract: Ependymomas are rare primary central nervous system (CNS) tumors in adults. They occur most commonly in the spinal cord, and have classically been graded histologically into World Health Organization (WHO) grades I, II, or III based on the level of anaplasia. Recent data are showing that genetic heterogeneity occurs within the same histological subgroup and that ependymomas arising from different CNS locations have different molecular signatures. This has renewed interest in developing targeting therapies based on molecular profiles especially given the variable outcomes with radiation and the poor results with cytotoxic agents. In this paper, we present the case of a 46-year-old woman with a classic presentation of spinal cord ependymoma and discuss the current histopathological and molecular classification for ependymomas as well as current guidelines for patient management.